Pengaruh Rekrutmen dan Pelatihan Kerja Terhadap Kinerja Karyawan Pada PT. Brinks Solutions Indonesia - Dewi Salsabilla, Natasya; Frida Aprillia (PT. Karya Inovatif Nusantara, 2025)
Recruitment and job training are interrelated to create optimal company performance. When employees have the skills and competencies needed by the company, the company will also have optimal performance. This study examines the effect of recruitment and job training on employee performance at PT. Brinks Solutions Indonesia with a quantitative descriptive method. Data were collected through questionnaires from 70 respondents and analyzed using multiple linear regression. The results show that recruitment has a significant effect on employee performance with a significance value of 0.001, Tcount 3.345, and a coefficient of 0.418. Job training does not have a significant effect on employee performance with a significance value of 0.454, Tcount 0.753, and a coefficient of 0.119. Simultaneously, recruitment and job training also have a significant effect on employee performance with an Fcount value of 6.528 and a significance of 0.003. Descriptive data is a description of the information used in the study. This study aims to determine how recruitment and job training affect employee performance at PT. Brinks Solutions Indonesia. In this study, the recruitment variables (X1) and job training (X2) act as independent variables, while the employee performance variable (Y) functions as the dependent variable.